2008
DOI: 10.1007/s00497-008-0084-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of nitrous oxide gas applied as a polyploidizing agent during meiosis in lilies

Abstract: Nitrous oxide gas (N(2)O) can be used to produce polyploid plants, but the mechanism of action is unknown. The actin and microtubule cytoskeleton was observed in N(2)O-treated microsporocytes of Lilium spp 'Asiatic hybrid lilies' using fluorescence microscopy after staining with DAPI, FITC-conjugated tubulin antibody, and phalloidin-conjugated Alexa Fluor 546. Additionally, microsporocytes of L. longiflorum were observed with acetocarmine staining following N(2)O treatment. A typical metaphase I microtubule di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…Multiple spindle poles are visible at early prometaphase I. During mid-prometaphase I, the multiple spindle poles become concentrated into two poles, and the typical bipolar meiotic spindle is complete at metaphase I (Suzuki and Tanaka, 1999;Kitamura et al, 2009). Multiple spindles are a meiotic abnormality in which more than one spindle occurs in meiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple spindle poles are visible at early prometaphase I. During mid-prometaphase I, the multiple spindle poles become concentrated into two poles, and the typical bipolar meiotic spindle is complete at metaphase I (Suzuki and Tanaka, 1999;Kitamura et al, 2009). Multiple spindles are a meiotic abnormality in which more than one spindle occurs in meiosis.…”
Section: Discussionmentioning
confidence: 99%
“…In Lilium, Barba-Gonzalez et al (2006) showed that N 2 O fumigation produced mainly first division restitution (FDR) gametes, indicating a disruption in meiosis I. Furthermore, Kitamura et al (2009) showed in Lilium that microtubules were depolymerised during metaphase I, which prevented chromosomes from moving to the poles. Dewitte et al (2010b) tried to induce 2n pollen by submerging flower buds of Begonia in a trifluralin solution.…”
Section: Induction Of 2n Gametesmentioning
confidence: 99%
“…In Lilium, Barba-Gonzalez et al (2006) showed that N 2 O fumigation produced mainly first division restitution (FDR) gametes, which indicates a disruption of meiosis I. Furthermore, Kitamura et al (2008) showed in Lilium that microtubules were depolymerised during metaphase I, which prevented chromosomes from moving to the poles. However, cell plate formation was not inhibited.…”
Section: Discussionmentioning
confidence: 97%